THE ABILITY OF COMMON CARP CYPRINUS CARPIO TO DIGEST DIFFERENT CARBOHYDRATE SOURCES - Batool Hussain Hatam Al-Mhauwi; Alaa Tariq Abdul wahid; Adil Yousif Al-Dubaikel (Basrah Journal of Veterinary Research)
Oral carbohydrate administration tests were used to gain more insight into the ability of common carp Cyprinus Carpio to digest different sources of carbohydrates. Four carbohyd- rates were administered orally after the common carp were fasted for 24h. Blood was sampled from fish at selected time intervals from 1 to 4h. Higher blood glucose level(p